Examination of university students' attitudes towards biotechnological studies in terms of faculty and gender variables - ŞAHİN, FATMA (ELSEVIER SCIENCE BV, 2010)
The objective of this study is to investigate university students' attitudes towards biotechnological studies in terms of faculty and gender variables. 222 students from three faculties in one university attended in this study. A questionnaire developed by Dawson and Schibeci (2003), was administrated to the undergraduate students to assess their attitudes towards biotechnological applications. Results obtained from this study showed no statistical differences in terms of gender variable. Statistical significant differences (p<.05) were found between students from different faculties in terms of the results of the questionnaire and it was found that biology students were particularly supportive of biotechnological studies compared with science education and medical students. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Biotechnology; biotechnological applications; genetically modified organisms; university students; attitudes; HIGH-SCHOOL-STUDENTS; KNOWLEDGE